Corporate reorganisations in China : an empirical analysis / Zinian Zhang, University of Leeds. - Zhang, Zinian (Cambridge University Press, 2018)
The first comprehensive empirical study on corporate bankruptcy reorganizations in the second largest economy, China, investigating the formal corporate restructurings handled by China's courts between 2007 and 2015. The data and analysis presented in the book provide a unique lens from which China's newly-enacted Chapter 11-styled corporate reorganization law, both in the books and in practice, can be understood and from which the interaction between business and state in dealing with corporate bankruptcies in China could be better comprehended. This book benefits from the author's ten-year business law practice in China, and his insights on China's judicial and political system considerably enrich the arguments. In particular, this book sheds light on commencement of bankruptcy reorganizations, control models, corporate reorganization financing, value distribution, approval of reorganization plans and cross-border reorganizations under the China Enterprise Bankruptcy Law of 2006.